Pengembangan Formulasi Krim Pelembab Kulit Berbasis Ekstrak Sari Buah Mangga (Mangifera indica L.): Pendekatan Fungsional dan Kosmetika Alami - Suci, Nurul; Khairunnisa, Lia; Nasri, Nasri; Kaban, Vera Estefania (Talenta Publisher, 2024)
This study aimed to develop a formulation of mango fruit juice (Mangifera indica L.) as a moisturizing agent in the form of hand cream. The main component of mango, sucrose, has the ability to attract moisture from the air due to its hydroxyl groups, which helps reduce water evaporation from the skin. Mango juice was obtained by blending the mango pulp using a juicer, followed by the addition of 0.1% sodium metabisulfite as an antioxidant. The extract was then concentrated using a freeze-drying technique at -40Â°C and 2 atm pressure. The cream formulation developed was an oil-in-water (m/a) emulsion type, with mango fruit juice concentrations of 2.5%, 5%, 7.5%, and 10%. These were compared to cream containing 2% glycerin and a blank formulation. Various tests were conducted to evaluate the physical quality of the cream, including homogeneity, pH, stability, emulsion type, and irritation tests using a moisture-checker. The results showed that mango fruit juice was successfully formulated into a homogeneous m/a cream, with a pH ranging from 5.55 to 7.04, and remained stable for up to 12 weeks of storage. The cream formulated with mango juice was proven to increase skin moisture without causing irritation. The higher the concentration of mango fruit juice, the greater the moisturizing effect. The 2.5% concentration provided a moisturizing effect comparable to cream containing 2% glycerin. The best moisturizing effect was achieved at a 10% concentration, which increased skin moisture by up to 14.4% after 4 weeks of use. This mango juice is effectively used in m/a type creams as a skin moisturizer. Keyword: Mango fruit juice, cream, skin moisturizer